Selection of appropriate probiotic yeasts for use in dairy products: a narrative review - Sanaz Kazemi; Aziz Homayouni-Rad; Hossien Samadi Kafil; Vahideh Sarabi-aghdam; Payam Zeynolabedini; Bahareh pour Agha; Sevda Allah Madadi (Food Production, Processing and Nutrition)
Abstract Yeasts, with a history of approximately 5,000 years in food and medicinal applications, play a vital role in various industries. The advantages of these microorganisms include probiotic effects, phytate biodegradation, mycotoxin breakdown, and adsorption capabilities. Traditionally, research on probiotics has primarily focused on lactic acid bacteria and bifidobacteria; however, there is a growing global interest in incorporating yeast as a probiotic supplement. Notably, yeast species such as Saccharomyces, Candida, Debaryomyces, Yarrowia, and Kluyveromyces have been identified for their probiotic potential. These probiotic yeasts are commonly introduced into dairy products, including kefir, yogurt, kumis, and cheese. However, the compatibility of probiotic yeasts with dairy matrices, as well as the factors influencing their viability and functionality, remains a critical area of study. Ongoing research focused on exploring techniques to enhance yeast viability during processing, given that different strains may exhibit varying survival rates and probiotic properties. Consequently, probiotic yeasts represent a promising avenue for augmenting the health benefits of dairy products. This development prompts essential discussions regarding selecting suitable probiotic yeasts for specific dairy applications. This paper comprehensively examines the historical discovery, types, properties, and applications of probiotic yeasts in dairy products. It aims to shed light on their health effects while addressing the challenges associated with selecting the appropriate probiotic yeast to optimize the enhancement of dairy products. Graphical Abstract